Piezoelectric and electronic properties of hydrogenated penta-BCN: A computational study - Thanasee Thanasarnsurapong; Klichchupong Dabsamut; Tosapol Maluangnont; Jiraroj T‐Thienprasert; Sirichok Jungthawan; Adisak Boonchun (Journal of Applied Physics, 2021)
The pentagonal boron carbon nitride (penta-BCN) monolayer has been recently proposed as a new member of the pentagon-based two-dimensional nanosheets [Zhao et al., J. Phys. Chem. Lett. 11(9), 3501 (2020)]. By using density functional theory with the generalized gradient approximation, we have carried out detailed investigations of a hydrogenated penta-BCN sheet, where the pristine penta sheet is decorated with H atoms to the composition BCNH2. The hydrogenated penta-BCN (H-BCN) structure is mechanically, thermally, and dynamically stable. It has a wide and indirect bandgap of 4.46 eV, contrasting with the direct gap of 1.70 eV in pristine BCN. H-BCN is environmentally stable at 1 bar of H2 down to 10−10 bar; beyond this point, pristine BCN becomes more stable. Compared with penta-BCN, the components of the elastic modulus tensor C11 and C12 of hydrogenated penta-BCN are reduced, while C12 and C66 are increased. The strain tensors of piezoelectricity in H-BCN are d21=0.462,d22=0.213, and d16=1.03pm/V, which are lower than those of pristine penta-BCN. The hydrogenated BCN structure displays a higher spontaneous polarization Ps than penta-BCN (4.64 × 10−10 vs 3.38 × 10−10 C/m, respectively). The smaller in-plane Young's moduli Ea and Eb for H-BCN indicated that that they are softer than those for penta-BCN. Strain engineering can help tune electronic properties. In agreement with this claim, we found that the indirect gap of H-BCN was tunable from 4.46 to 3.26 eV under an applied tensile strain of 0%–16%, the range where the structure is dynamically stable throughout. Meanwhile, H-BCN is dynamically unstable under an applied compressive strain.
Keywords: Graphene research and applications; 2D Materials and Applications; MXene and MAX Phase Materials